PENGUJIAN SENSITIVITAS DAN AKURASI SENSOR ARUS HALL EFFECT MENGGUNAKAN ARDUINO-UNO - Limbran Sampebatu; Simon Patabang; Jeremias Leda (LPPM Universitas Bina Bangsa, 2022)
The sensitivity and accuracy of the hall effect current sensor is an important factor in its application considering that electric current is the main parameter in the study of electrical energy engineering, telecommunications and electronics. However, on the other hand, studies related to the sensitivity and accuracy of Hall effect current sensors are still rarely carried out. The method used in this research is an experimental laboratory study using the ACS712 sensor with a variation rating of 5A, 20A and 30A. The results show that the sensitivity is inversely proportional to the ampere rating of the ACS712 sensor where the greater the current rating of the sensor, the lower the sensitivity. While the accuracy is directly proportional to the ampere rating of the ACS712 sensor where the greater the current rating of the sensor, the more accurate the sensor is